Reed's syndrome - Filipa Tavares Almeida; Rui P Santos; Sofia D Carvalho; Maria C Brito (Wolters Kluwer Medknow Publications, 2018)
Multiple cutaneous and uterine leiomyomatosis (MCUL), also known as Reed's syndrome, is a rare genodermatosis, with an autosomal dominant pattern of inheritance. It results from a germline heterozygous mutation of fumarate hydratase gene, that is classified as a tumor suppressor gene. Hereditary leiomyomatosis and renal cell cancer is characterized by the association of MCUL with renal cell carcinoma. We report a case of a 57-year-old woman, with multiple cutaneous leiomyomas as the presenting sign of Reed's syndrome.